Внутрішній контроль витрат періоду підприємства - Бойчук, Т. М. (Видавництво Львівської політехніки, 2014)
Досліджено основні особливості формування системи внутрішнього контролю витрат періоду підприємства. Проведено аналіз дефініцій понять “внутрішній” та “внутрішньогосподарський” контроль, розкрито принципові підходи до його організації. Визначено взаємозв’язок контролю з іншими функціями управління витратами. На основі комплексного підходу здійснено побудову системи внутрішнього контролю. Визначено мету, сформульовано основні завдання, а також виокремлено об’єкт та суб’єкт внутрішнього контролю витрат періоду. Розкрито методику та організацію внутрішнього контролю витрат періоду. Internal control takes important place in enterprise costs management system plays. Due to the application of its principles and methods inappropriate and excessive costs can be detected and prevented. The value of internal control can’t be overstated, the most urgent this issue is for large enterprises management system, where a variety of costs requires a specific approach to their control. Also, the same important value has internal control organization for shareholders and investors. In this case the control can be regarded as a voucher of effective enterprise management. At the same time, insufficient attention is paid to internal cost control in practice. The main reason is the lack of workers knowledge and inability to apply the method of internal control implementation. Another problem with the organization of effective control organization is an absence of scientific approach to control organization depending on the type of expenditure. Its worth to notice, that the type of costs (production costs, auxiliary department costs, administrative, marketing etc) requires the organization of internal control directly to their nature, structure and behavior. Many concepts of internal control are offered currently concerning production costs, but there isn’t a big amount about period costs, which are not included to the production cost, but directly affect the financial results formation. The structure of period costs during operational activity includes administrative, marketing and other operating costs. Purpose of research. To discover the essence of internal control according to the integrated approach, to define its aim, tasks, objects and subjects according to the systematic approach, and to disclose organizational aspects of internal control on enterprise’s period cost example. Object of research is an costs’ internal control system, which are directly unrelated to the production process: administrative, marketing and other enterprise’s operating costs. The subject of research is theoretical, methodological and applied aspects of costs’ internal control.
Internal control of period costs of enterprise
Keywords: внутрішній контроль; система внутрішнього контролю; витрати періоду; internal control; internal control system; period costs